Sweet peril - Higgins, Wendy (Higgins, Wendy. Sweet trilogy, 2013)
"An unexpected lost message from the angels surfaces, and sweet Southern girl Anna, daughter of a guardian angel and a fallen one, finds herself traveling the globe in an attempt to gain support for her cause from fellow Nephilim. Meanwhile, her true love, Kaiden Rowe, the son of the Duke of Lust, is plaguing her heart and mind"--